Synopsis of the Evippinae (Araneae, Lycosidae) of Israel, with description of a new species - Armiach Steinpress, Igor; Alderweireldt, Mark; Cohen, Mira; Chipman, Ariel; Gavish-Regev, Efrat (European Journal of Taxonomy, 2021)
Evippinae (Araneae, Lycosidae) is a subfamily of old-world lycosids, comprising six genera and 67 species, most of them typically found in xeric habitats. Although Israel is located between the two distribution-centers of the subfamily, Africa and central Asia, only two species of the genus Evippa Simon, 1882, namely E. arenaria (Audouin, 1826) and E. praelongipes (O. Pickard-Cambridge, 1871), and a doubtful record of Xerolycosa nemoralis (Westring, 1861) were reported previously. Here we describe a new species: Evippa amitaii sp. nov., and re-describe and report a new record for Israel of E. onager (Simon, 1895 sensu Šternbergs 1979). Additionally, the genus Evippomma Roewer, 1959 is recorded for the first time from the Middle East, with a description of the previously unknown female of Evippomma simoni Alderweireldt, 1992. We discuss the possible vicariance of Evippa arenaria and E. praelongipes. We suggest that the dispersal of E. arenaria along the coastal plain is blocked by the Yarqon river valley. We suggest competition with a similar species (Pardosa subsordidatula (Strand, 1915)) as a factor affecting the seasonal activity of E. arenaria. Additionally, we present a partial molecular phylogeny of Evippinae, to clarify the placement of E. onager, a species with an unusual morphology.